Features of pea seed germination under the effect of an extract from the mycelium substrate for oyster mushroom cultivation - S. S. Tarasov; E. V. Mikhalev; E. K. Krutova; I. V. Predeina (Труды по прикладной ботанике, генетике и селекции)
Background. The presented study demonstrates the ability of an aqueous extract from the used straw substrate for oyster mushrooms (hereinafter referred to as “the extract”) to regulate pea plant growth and development.Materials and methods. Experimental seeds of the pea cultivar ‘Albumen’ were soaked in 10% and 100% extracts and then cultivated for eight days on a hydroponic medium in the respective extract solutions and on soil (gray forest). The control plants were soaked in tap water, cultivated in it (hydroponics), and watered (soil). The extract’s effectiveness was assessed according to growth indicators, the content of photosynthetic pigments, and the expression of one of the genes encoding ribulose bisphosphate carboxylase/oxygenase activase (RCA) and two genes encoding isoamylase (ISA-1 and ISA-2).Results. Inhibition of seed germination on the first day under the effect of 10% and 100% extracts was shown. Higher dry matter content and a decrease in the expression of all ISA genes were observed in the day-old germinating experimental seeds, indicating a slowdown in the initiation of seed germination. A decrease in the germination rate was recorded in the seeds cultivated with the 100% extract, while for those germinated with the 10% extract, this indicator did not differ from the control. The content of photosynthetic pigments in the experimental plant groups (100% concentration of the extract) grown in hydroponics was lower, and in those grown on soil, it was higher than in the control samples.Conclusion. The extract in both doses suppressed the germination of pea seeds and inhibited the growth and development of seedlings when cultivated on a hydroponic medium consisting of the extract. However, enhanced growth processes and increased expression of the studied genes were observed when pea plants were watered with the extract in a soil environment.